Peran Arsiparis dalam Pengelolaan Otomasi Arsip di Dinas Perpustakaan dan Kearsipan Aceh - Mastura, Fielda; nurdiansyah, aulia (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
The use of Information and Communication Technology (ICT) in archive management, also known as "Archive Automation". In automation-based archive management, every agency requires an archivist who has special knowledge and expertise in archive management and an understanding of information technology. Librarians and archivists' expertise in information technology has a central role in managing digital collections. The purpose of this research is to see how a professional archivist handles archival automation. The object of this research is the role of archivists in the Aceh Library and Archives Service. This study used descriptive qualitative method. This method aims to explain the role of archivists in managing archive automation at the Aceh Library and Archives Service. Data collection was carried out by looking at websites and reading literature from a number of journal articles. Based on the results from the website https://arpus.acehprov.go.id/, the existence of this institution as a digital library plays a major role in providing access to information, optimizing the use of technology, and increasing people's interest in reading in accordance with the responsibilities and roles they carry out.